Millipedes as Food for Humans: Their Nutritional and Possible Antimalarial Value—A First Report. (12th February 2014) - Enghoff, Henrik; Manno, Nicola; Tchibozo, Sévérin; List, Manuela; Schwarzinger, Bettina; Schoefberger, Wolfgang; Schwarzinger, Clemens; Paoletti, Maurizio G.
Abstract : The first record of millipedes (Diplopoda) being regularly used for food by humans (the Bobo people of Burkina Faso) is given, including information on how the millipedes are prepared. The species in question are Tymbodesmus falcatus (Karsch, 1881) and Sphenodesmus sheribongensis (Schiøtz, 1966) (Gomphodesmidae) and an unidentified species of Spirostreptidae. New information on the nutritional value of millipedes is provided; unsaturated fatty acids, calcium, and iron contents are particularly high. The millipedes' defensive secretions, hydrogen cyanide and benzoquinones, present a severe challenge for the spread of millipedes as an everyday food source. On the other hand, the possibility that benzoquinones may act as insect-repellents, as known from studies on nonhuman primates, and that sublethal cyanide ingestion may enhance human innate resistance to malaria, suggests promising ethnomedical perspectives to our findings.